Seasonal and Temporal Drivers Influencing Phytoplankton Community in Kuwait Marine Waters: Documenting a Changing Landscape in the Gulf - Devlin, Michelle J.; Breckels, Mark; Graves, Carolyn A.; Barry, Jon; Capuzzo, Elisa; Huerta, Francisco P.; Al Ajmi, Fahad; Al-Hussain, Mona M.; LeQuesne, William J. F.; Lyons, Brett P. (Frontiers in Marine Science, 2019)
This assessment of environmental drivers and phytoplankton community in Kuwait (Arabian Gulf) describes changes in environmental conditions linked to the rapid urbanization over recent decades. To describe these changes, we have analyzed a long-term water quality dataset (1984–2017) and explored potential changes in a sub-set of phytoplankton community data by analyzing 10 years of phytoplankton data available (2007–2016) for Kuwait Bay and the Northern Gulf waters. The longer-term water quality data show that dissolved nutrient concentrations, with the exception of a recent fall in SiO4, have been increasing over 30 years, but with a high degree of variability reflecting the changing rate of inputs from river outflows and point sewage sources. The correlative analysis between the environmental parameters and phytoplankton in the period from 2007 to 2016 shows that the seasonal variability of the phytoplankton are influenced by several co-stressors including higher temperatures, coastal sewage runoff and changing salinity. While the extended nutrient enrichment has changed the trophic state of Kuwait waters, the seasonal and temporal correlations highlight that recent changes in phytoplankton community seem to be responding to cumulative pressures of eutrophication, climate, and salinity changes. The seasonal and temporal changes in the coastal phytoplankton community, responding to co-stressors, present challenges for managers to consider the simultaneous management of local, regional and external pressures. Continued declines in water quality within a system that is influenced by a warming climate can potentially have long-term consequences on the resilience of the Northern Gulf environment.